Gastrointestinal endoscope contamination rates – elevators are not only to blame: a systematic review and meta-analysis - Goyal, Hemant; Larsen, Sara; Perisetti, Abhilash; Larsen, Nikolaj Birk; Ockert, Lotte Klinten; Adamsen, Sven; Tharian, Benjamin; Thosani, Nirav (Endoscopy International Open, 2022)
Background and study aims Duodenoscopes that are contaminated due to inadequate reprocessing are well-documented. However, studies have demonstrated poor reprocessing of other kinds of endoscopes as well, including echoendoscopes, gastroscopes, and colonoscopes. We estimated the contamination rate beyond the elevator of gastrointestinal endoscopes based on available data.Methods We searched PubMed and Embase from January 1, 2010 to October 10, 2020, for studies investigating contamination rates of reprocessed gastrointestinal endoscopes. A random-effects model was used to calculate the contamination rate of patient-ready gastrointestinal endoscopes. Subgroup analyses were conducted to investigate differences among endoscope types, countries, and colony-forming unit (CFU) thresholds.Results Twenty studies fulfilled the inclusion criteria, including 1,059 positive cultures from 7,903 samples. The total contamination rate was 19.98 % ± 0.024 (95 % confidence interval [Cl]: 15.29 %–24.68 %; I2 = 98.6 %). The contamination rates of colonoscope and gastroscope channels were 31.95 % ± 0.084 and 28.22 % ± 0.076, respectively. Duodenoscope channels showed a contamination rate of 14.41 % ± 0.029. The contamination rates among studies conducted in North America and Europe were 6.01 % ± 0.011 and 18.16% ± 0.053 %, respectively. The contamination rate among studies using a CFU threshold > 20 showed contamination of 30.36 % ± 0.094, whereas studies using a CFU threshold < 20 showed a contamination rate of 11 % ± 0.026.Conclusions On average, 19.98 % of reprocessed gastrointestinal endoscopes may be contaminated when used in patients and varies between different geographies. These findings highlight that the elevator mechanism is not the only obstacle when reprocessing reusable endoscopes; therefore, guidelines should recommend more surveillance of the endoscope channels as well.